PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL (Studi pada Guru PNS SMP di Kecamatan Ulujami Kabupaten Pemalang) - Prijatno Sri Eko Putranto, 1352020069; Sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to investigate the influence of motivation and discipline to the performance of teachers with organizational culture moderated. The specific objectives are to test and analyze the effect of motivation on the performance of teachers, discipline influence on teacher performance, the influence of organiza-tional culture on teacher performance, organizational culture moderates the effect of motivation on teacher performance and the moderating influence of organizati-onal culture on teacher performance discipline. Research conducted an explanatory research study that proves the influence of motivation and discipline on teacher performance moderated organizational culture that has been formulated in the hypothesis. The population in this study is a teacher of Civil Servants Junior High School Ulujami the District Pemalang totaling 127 people from five (5) Junior High School. The research data is primary data obtained directly from the respondents to the questionnaire. If the data from respondents using SPSS version 22. From the test data and analysis conducted this study provide empirical evidence as follows: 1) Motivation positive and significant impact on teacher performance; 2) Discipline positive and significant impact on teacher performance; 3) influence of organizational culture on teacher performance; 4) organizational culture does not moderate the effect of motivation on teacher performance; 5) organizational culture does not moderate the influence of discipli-ne on teacher performance. Theoretical implications, and recommendations for fu-ture research are also discussed in the final part in this study. Keywords: Motivation, Discipline, Organizational Culture, Teacher Performance